Latin American Entrepreneurs: Many Firms but Little Innovation - Lederman, Daniel (World Bank, 2015)
Entrepreneurship -- manifested in the entry of new firms or products into new markets, or substantial improvements in technological capacity or process innovation by incumbent firms -- is widely considered to be an important ingredient for long term economic development. This report argues that entrepreneurship is also a source of employment generation, export growth, and resilience during economic downturns. Although the conventional wisdom suggests that Latin American and Caribbean countries underperform relative to China and other emerging markets in terms of its entrepreneurial dynamism, this report provides evidence suggesting that the region is characterized by substantial entrepreneurship. The main challenge in the region is not a lack of entrepreneurs, but rather their relatively low level of innovation and the slow growth of incumbent firms. The report discusses the nature of new entrants into markets and the factors that might help stimulate private-sector innovation after firms have survived the initial test of market competition.